Hooks and Endings in Magazine Articles to Engage Readers - Ting, Su Hie; Jacqueline Siaw, Chin Chin (Human Behavior, Development and Society, 2020)
In view of the lack of research on types of hooks and endings which are commonly used in articles for leisure reading, this study examined hooks and endings in magazine articles. A total of 19 articles from Kuching In and Out (KINO) magazine published in Malaysia were selected for analysis (6 by males, 13 by females). The most common types of hooks to draw readers into the next sentence and set the tone for the rest of an article were flashback, description, and facts. Flashback and self-introduction were new, probably due to the nature of the KINO magazine which features the life experiences of writers from Kuching who are presently living in other parts of the world. Less-frequently used hooks were empathy, mystery, plot twist, and questions. Most endings were a return to the writer’s hook or information mentioned earlier in the article, taking the form of reflections or issue resolution, as well as two other less-used endings, questioning and giving revelations. An ending that was different was taking leave, which reflected a talking style similar to “a good-bye” in social interactions. The study suggests that some hooks and endings are specific to the subject matter and readership of magazines.